2019
DOI: 10.1111/dth.12956
|View full text |Cite
|
Sign up to set email alerts
|

Calcipotriol ointment shows comparable efficacy to topical steroids in chronic hand eczema

Abstract: Topical potent corticosteroids are the mainstay of treatment for chronic hand eczema (CHE). However, there are numerous adverse effects associated with the chronic use of topical corticosteroids. Calcipotriol has been widely used in psoriasis and has been reported to achieve beneficial effects in several inflammatory diseases. This study aimed to evaluate the efficacy and safety of calcipotriol ointment compared to desoximetasone ointment in the treatment of CHE. Patch testing was performed in all recruited su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
0
13
0
2
Order By: Relevance
“…39,54,55 Calcipotriol affects epidermal cells by prohibiting proliferation, angiogenesis, and cytokine production, and regulates hapten-induced immune responses by dendritic cells, 1,39,54 but its widespread use is limited by common side effects such as skin scaling, dryness, and irritation. 55,56 Case reports of several patients have shown improvements in hand eczema after treatment with topical calcipotriol, 39,54 and a recent prospective, randomized trial found that 0.005% calcipotriol was as effective as topical steroids in improving clinical severity of hand eczema. 55 Calcineurin inhibitors, another class of existing topicals, are frequently used in the treatment of mild to moderate chronic hand eczema.…”
Section: Existing Topical Therapeuticsmentioning
confidence: 99%
“…39,54,55 Calcipotriol affects epidermal cells by prohibiting proliferation, angiogenesis, and cytokine production, and regulates hapten-induced immune responses by dendritic cells, 1,39,54 but its widespread use is limited by common side effects such as skin scaling, dryness, and irritation. 55,56 Case reports of several patients have shown improvements in hand eczema after treatment with topical calcipotriol, 39,54 and a recent prospective, randomized trial found that 0.005% calcipotriol was as effective as topical steroids in improving clinical severity of hand eczema. 55 Calcineurin inhibitors, another class of existing topicals, are frequently used in the treatment of mild to moderate chronic hand eczema.…”
Section: Existing Topical Therapeuticsmentioning
confidence: 99%
“…A recent prospective study in 13 patients with in-patient control compared the efficacy of calcipotriol ointment with desoximetasone ointment, a superpotent glucocorticosteroid, twice daily for 8 weeks. 43 The hand eczema severity index (HECSI) scores revealed up to a 75% reduction in both treatments (P < 0.001) without significant differences between the groups (P > 0.05). 43 Thus, calcipotriol may have a potential as a steroid-sparing agent in the management of hand eczema.…”
Section: Topical Calcipotriolmentioning
confidence: 94%
“…43 The hand eczema severity index (HECSI) scores revealed up to a 75% reduction in both treatments (P < 0.001) without significant differences between the groups (P > 0.05). 43 Thus, calcipotriol may have a potential as a steroid-sparing agent in the management of hand eczema. Clearly, further studies are necessary including more patients and differentiating better between hand eczema and psoriasis.…”
Section: Topical Calcipotriolmentioning
confidence: 94%
See 1 more Smart Citation
“…Es wird diskutiert, dass die Behandlungszeit im Therapiearm zu kurz gewählt worden war [10]. Calcipotriol, als topisches Therapeutikum bei Psoriasis bekannt, konnte beim CHE bei allen klinischen Typen gute Wirkung zeigen [11]. Bei atopischem Handekzem mit Therapieversagen auf die üblichen systemischen Immunsuppressiva der bisherigen Leitlinie war Dupilumab effektiv.…”
unclassified